A Case Study: Second Language Investments of an International Student in Shaping Identity - Devi Mulyani (Pusat Studi Pendidikan Bahasa dan Sastra Inggris, 2018)
AbstractThe objective of this study is to find the ways of a postgraduate student in investing in the shaping of her second language identity in the local communities of practice in a city in the UK. This research is a case study which employs qualitative descriptive method. Data was gathered through diaries and interviews. It is found that the subject, Jasmine, was active in the communities. She knew how she should invest her English in there although she was not too confident with her English. She involved in several communities in the UK, for example meeting with people in the church, visiting the local family, gathering in the cafe, and involving in the English study club. She did not find limitation to speak English from the native speakers in the communities. This implies that she found who herself and how she should invest in the societies. These finally shape her identity as a second language learner in the local communities. In conclusion, her investment in the local communities has shaped her second language identity. Key Words: Second Language Learner, investment, identity